2017
DOI: 10.1364/josaa.34.000674
|View full text |Cite
|
Sign up to set email alerts
|

Fresnel diffraction from a step in the general case

Abstract: Recently, Fresnel diffraction from phase steps with parallel plates has been studied in detail, and the subject has led to many interesting metrological applications. In this report we formulate Fresnel diffraction from a physical step with arbitrarily oriented plates in reflection mode. We simulate the diffraction patterns for different orientations of the plates and develop the required procedure for determining the involved angles by analysis of the diffraction pattern. In the experimental part of the repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For 1 t  , Eq. (10) reduces to [16]: V is a universal curve for 0  in the interval of 02   . This allows us to specify the experimental normalized intensity profiles accurately by fitting them on the corresponding universal curves.…”
Section: Fresnel Diffraction From a Phase Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…For 1 t  , Eq. (10) reduces to [16]: V is a universal curve for 0  in the interval of 02   . This allows us to specify the experimental normalized intensity profiles accurately by fitting them on the corresponding universal curves.…”
Section: Fresnel Diffraction From a Phase Stepmentioning
confidence: 99%
“…Derivation of the amplitudes and phase difference for wavefronts emerging from a phase step with arbitrary orientation of its surfaces is rather complex [13,16]. Therefore, we do not consider here, and conclude the section by presenting some relevant simulations.…”
Section: Sohmentioning
confidence: 99%
“…Recently it has been shown that discontinuous changes in phase or phase gradient of the light beam leads to an appreciable diffraction that is referred to as Fresnel diffraction from phase steps [11,12]. This effect was studied theoretically and experimentally [13,14], and applied to a plenty interesting metrological measurements. The measurements include refractive indices of materials with high accuracy [15][16][17][18], nonlinear refractive index [19], thickness of thin films and plates [20], nanometer displacement [21], wavelength, and spectral line profile [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, Fresnel diffraction from a phase step is studied [27][28][29] and widely considered in the context of different metrological applications, e.g., the measurement of refractive indices of solids and liquids [30][31][32], thickness of films and plates [33], focal length of an imaging system [34], etching rate of glass steps [35], and determination of the off-axis angle and the wavelength of light [36].…”
Section: Introductionmentioning
confidence: 99%